The Football Passing Technique Skills - Vega Soniawan; Yogi Setiawan; Eval Edmizal; Jeki Haryanto; Ikhwanul Arifan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This research is conducted due to the problems in football, where some players tend to do wrong passing, inaccurate passing, and lack of passing power and quality. The research aims to describe the football passing technique skills in using the inside of the foot in terms of movement quality (preparation phase, impact phase, and follow-through) and result quantity of the football passing skills. The subjects were 30 football players from UNP Football Club. The data collection was conducted through video observation assessed by the football experts and using the football short passing test instrument. Based on the data analysis, it is found that the average of about 10.13 (80.28%) in terms of movement was also categorized as sufficient. Thus, the football coaches in UNP Football Club can improve the football passing technique regarding movement quality and result quantity in each football exercise process.